Implementasi Pembelajaran Integrasi Ilmu Pengetahuan Alam Dengan Matematika Untuk Meningkatkan Keterampilan Proses Sains Mahasiswa - Iqbal Limatahu; Chumidach Roini; Tuti Gailea; Dyana Umanailo; Risnawati Sadali; Jani Fatgehipon; Djaitun Hardin; Dwi Sukmawati A. Yusup; Bangbang Taryono (EDUKASI, 2025)
The integration of Natural Sciences (IPA) with Mathematics is an important requirement in 21st-century science education to develop students' critical thinking, creative thinking, and numeracy literacy. This study aims to analyze the implementation of integrated learning of Science and Mathematics based on the CCDSR (Condition, Construction, Development, Simulation, Reflection) model in improving the science process skills of students in the Master of Science Education Study Program, Universitas Khairun in the Integrated Science Studies course. The method used is a pre-experimental one group pretest–posttest design with a sample of 12 students in the odd semester of 2025. The results of the study showed a significant increase in science process skills (SPS) with an average N-gain in the medium-high category (0.62-0.88). This finding confirms the importance of innovative model-based science-mathematics integration to improve students' scientific thinking skills.